No End In Sight - Ferguson, Charles (Representational Pictures, 2007)
Verzio FF Submission "No End In Sight" is a scrupulous overview of the Iraq-war debacle and runs through a litany of horrors so relentless it borders on farce. The facts speak for themselves in this sober yet enraging documentary, which traces the fateful decisions to a small circle of hawks acting on behalf of a president who seems to have been a clueless outsider in his own administration.